The Effect of Using Rome IV Criteria on the Prevalence of Functional Abdominal Pain Disorders and Functional Constipation among Children of the Western Region of Saudi Arabia - Ammar Khayat; Ghady Algethami; Sama Baik; Mai Alhajori; Dhayy Banjar (SAGE Publishing, 2021)
Functional gastrointestinal disorders are characterized by absence of anatomical and biochemical alterations, and are diagnosed and classified based on symptomatology. We aim to explore the prevalence of functional abdominal pain disorders and Functional constipation using Rome IV criteria. An online questionnaire was distributed randomly via social media targeting the general population of the western region of Saudi Arabia. Parents who have at least 1 child in the age group 3 to 18 years were included. Children with mental disabilities, or any organic gastrointestinal disorder were excluded. Five hundred thirty-two responded and 215 were excluded. The overall prevalence of functional abdominal pain disorders was 3.1%. The prevalence of functional constipation was 4.7%. Conclusions : Rome IV criteria seems to give a lower functional abdominal pain prevalence than Rome III, online learning did not seem to affect the prevalence of both disorders, but a family stressor seems to increase functional constipation prevalence.